Enhancing Efl Students’ Speaking Confidence and Engagement Through Photovoice-Based Board Games - Hasby, Nazar; Indra Perdana; Natalina Asi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aimed to describe how the application of Photovoice-Based Board Games increased students' confidence and engagement in speaking English. The background of this research stemmed from the issue of Indonesian students’ low confidence in speaking English in class, which was caused by anxiety, limited vocabulary, and teacher-centered learning methods. The study employed a qualitative approach with a case study design. Data were collected through observation and interviews with a group of high school students in Kalimantan who participated in Photovoice-based learning activities and board games. The findings indicated that these activities enhanced student engagement by fostering a fun and collaborative learning atmosphere. They also boosted students’ confidence in speaking through visual reflection and social support within the classroom. However, several challenges remained, such as limited vocabulary and difficulty in organizing ideas. Overall, Photovoice-Based Board Games proved to be a practical and innovative approach to developing EFL students’ speaking skills in a pressure-free and meaningful learning environment.